ISU-ISU PEMBAHARUAN ISLAM DI BEBERAPA NEGARA PERSPEKTIF SEJARAH - Dewi, Rusmala (Universitas Islam Negeri Raden Fatah Palembang, 2016)
The collapse of the Abbasid sovereignty at the end of the period 635 H / 1258 AD political Islam has caused the loss of influence in the world. Even after the fall of the Abbasid caliphate was established in the form of several dynasties and kingdoms, such as; Mughal empire in India, Safavid empire in Persia and the Ottoman Empire in Turkey. However, the establishment of the dynasty and the government is not much help because it only operates in the field of internal development of science. In fact even the emergence of dynasties that only widen the political disintegration of the Muslim world. No doubt in the last phase of the decline of the Islamic caliphate, the Ottoman Caliphate since turned into a secular country that pioneered by Mustafa Kemal. The chronic backwardness of Islam, on the other hand Europe (Western World) revolutionized civilization as aukflarung renaissance, and rationalism that gives excesses of the industrial revolution in Europe. This article will discuss about the issues of reform in the Islamic world historical perspective.تسبب انهيار لسيادة العباسية في نهاية الفترة 635 ه / 1258 م الإسلام السياسي فقدان نفوذها في العالم. حتى بعد قيام سقوط الخلافة العباسية في شكل عدة السلالات والممالك، مثل: إمبراطورية المغول في الهند، الإمبراطورية الصفوية في بلاد فارس والإمبراطورية العثمانية في تركيا. ومع ذلك، وإنشاء أسرة والحكومة لا تساعد كثيرا لأنها تعمل فقط في مجال التنمية الداخلية من العلم.في الواقع حتى ظهور السلالات التي توسع فقط التفكك السياسي للعالم الإسلامي.لا شك في المرحلة الأخيرة من ضعف الخلافة الاسلامية، الخلافة العثمانية منذ تحولت إلى دولة علمانية التي كانت رائدة على يد مصطفى كمال.التخلف المزمن من الإسلام، من ناحية أخرى أوروبا (العالم الغربي) ثورة الحضارة مثل النهضة، والعقلانية التي تعطي تجاوزات الثورة الصناعية في أوروبا.هذه المادة سوف يناقش حول قضايا الإصلاح في منظور تاريخي العالم الإسلامي.